Optimalisasi Pengelolaan Limbah Kelapa Melalui Pembuatan Briket Arang : Solusi Ekonomi dan Lingkungan di Desa Lampuyang - Bayu Virdaus; Nur Arifin; Muhammad Sulhan Aziz; Nur Alisa; Nur Aisyah; Nur Azizah; Nulia Putri Erayani (FKIP, Universitas Palangka Raya, 2024)
Kuliah Kerja Nyata (KKN) or Community Service Program is a student engagement initiative designed to apply academic knowledge and skills in real-world contexts. The KKN program in Lampuyang Village, Teluk Sampit District, Central Kalimantan, conducted from July 15 to August 29, 2024, focused on converting coconut shell waste into charcoal briquettes. Lampuyang Village possesses significant potential in coconut plantation, but the waste from coconut, such as shells and husks, is often underutilized. This KKN aimed to provide a solution by training the village’s youth in making charcoal briquettes, thereby enhancing their skills and creating new, environmentally friendly business opportunities. Through a Participatory Action Research (PAR) approach, the program actively involved the community at every stage, from observation, planning, implementation, to evaluation. As a result, the program raised awareness about the economic potential of coconut waste, reduced environmental impacts from open burning, and encouraged the youth to engage in local economic development. This initiative is expected to offer long-term benefits to Lampuyang Village’s community and strengthen the role of students as agents of social change.